Avaliação de adsorventes sólidos para a remoção de derivados de HPAs em solução - Colim, Alexsandro Nunes (2014)
Polycyclic aromatic hydrocarbons, nitrogen and oxygen (Nitro-PAHs and Oxy-PAHs) compose the class of compounds where a hetero atom of nitrogen and oxygen, respectively, is present in the constitution of the HPA. The inclusion of a heteroatom leads to increased mobility and increased toxicological potential. In this work were investigated adsorbent materials for removal of Nitro-PAH and Oxy-PAH from aqueous solutions. For this purpose, activated carbon (AC), polyurethane foam (PUF), quartz fiber (QF), high density polyethylene (PEHD), polytetrafluoroethylene Teflon (PTFE), Amberlite XAD-2 (XAD-2) and silica gel (Si), were evaluated as potential solid substrates, as well as its use as an alternative to XAD -2 for making personal samplers type lapel. Quinoline, 1-nitronaphthalene, Acridine, Phenazine, 2-nitrofluorene, 9-nitroanthracene and 1-nitropyrene were chosen as representatives of the class of compounds Nitro-PAHs. 2-naphthol, 2-hydroxyfluorene, Phenanthrene-9-carboxaldehyde, 9,10-anthraquinone, and 1-hydroxypyrene were chosen as representatives of the class of compounds Oxy-PAHs. The results were obtained by batch tests. For Nitro-PAHs, the adsorbents with the highest removal rates were: XAD-2 (100% removal on XAD-2, except for Quinoline - 80%) and activated carbon (around 90% for all reviews compounds). For Oxy-PAHs, the highest removal rates were provided by adsorbents: polyurethane foam and activated carbon, both with rates higher than 90% of removal. Due to the low solubility of the compounds, the presence of a co-solvent is required. The lowest temperature (20 ⁰C) favored the adsorption of the compounds. In general, both (Nitro-PAHs and Oxy-PAHs) classes have their removal influenced by increasing the concentration of the solute in solution.